Suurten yritysten ja niiden arvoketjujen rooli taloudessa; The Role of the Largest Companies and Their Value Chains in the Economy - Jyrki Ali-Yrkkö; Timo Seppälä; Juri Mattila (The Research Institute of the Finnish Economy (ETLA), 2016)
– This report analyzes the role of the largest companies in the Finnish economy. According to the results, the ten largest companies in terms of their value added together produce 7,6 % of the Finnish GDP. In addition, these companies generate notable multiplicative effects in the economy. According to the findings, the productivity and the growth rates of the ten largest companies clearly surpass the economy average. In this study, it was also analyzed what kinds of macroeconomic effects will generated by Metsä Fibre's investment into their new bioproduct factory in Äänekoski, Finland. The calculations were conducted for the construction phase and the production phase individually. According to these analyses, the construction phase alone will generate a positive impact on employment reaching thousands of man-years. However, the true significance of the investment will only become evident in the production phase, since not all investments of equal scale produce similar macroeconomic effects. Besides the characteristics of the examined industries, the size of these effects also depends on which countries acquisitions are made from.
Keywords: F23; L25; E22; M21; L11; 330; Large; Largest; Companies; Firms; GDP; Productivity; Gross domestic product; Concentration; Multiplier effect; Investment; Pulp; Äänekoski; Group; Granular; Concentration; Großunternehmen; Wertschöpfung; Bruttoinlandsprodukt; Produktivitätsentwicklung; Multiplikator; Finnland